Hubungan Kualitas Pelayanan Keperawatan Dengan Kepuasan Pasien Rawat Jalan di RSBT Karimun Tahun 2023 - Martha Dwi Novalia; Umi Eliawati; Utari Christya Wardhani (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2024)
The quality of health services is a manifestation of the results of the performance of health workers which results in patient satisfaction, if the service meets or exceeds what the patient expected (Antari, 2019). Service quality is assessed from five variables, namely Reliability, Responsiveness, Physical Evidence, Guarantee and Empathy. The aim of the research was to determine the relationship between the quality of nursing services and the level of outpatient satisfaction at RSBT Karimun in 2023. The research carried out was descriptive correlational research and a cross-sectional approach. The sampling method used was consecutive sampling with a sample size of 174 outpatients at Bakti Timah Karimun Hospital in 2023. Research data was collected by filling in questionnaires by respondents. The research data were analyzed univariately with frequency tables and bivariate tests with the Chi Square test. The results of the univariate analysis show a picture of Service Quality from the reliability variable. The results of the bivariate analysis of the Reliability and Satisfaction variables were obtained, so it can be concluded that there is a significant relationship between service quality and satisfaction of outpatients at Bakti Timah Karimun Hospital in 2023. It is hoped that this research's suggestions will enable the educational institution at Awalbros University, Batam, to increase nurses' knowledge about the quality of nursing services. to increase patient satisfaction.